ChemInform Abstract: Pd‐Catalyzed Direct C2‐Acylation and C2, C7‐Diacylation of Indoles: Pyrimidine as an Easily Removable C—H Directing Group. Issue 32 (August 2015) - Kumar, Govindharaj; Sekar, Govindasamy
Abstract The reaction proves successful using aryl, hetaryl, alkyl, and alkenyl aldehydes as acylation agents.